Cleome rutidosperma DC.- a New Record for India - Mukherjee, P. K. (Indian Forester, 1969)
Cleome rutidospenna DC. (Capparaceae), a native of Africa but naturalised in Burma and Malaysia, is now recorded from W. Bengal.